Bibliometric Analysis: Research Trend of Interactive Learning Media in Mathematics Learning in Indonesia - Muhammad, Ilham; Mukhibin, Ahmad; Naser, Abdurrahman do muhamad; Dasari, Dadan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Interactive learning media is a combination of videos, animations, images, and audio on learning media that allows users to interact and understand the material because the learning process becomes interesting, interactive, and effective. The trend of publications that have the highest number of citations, the classification of university or organization rankings, journals and publications, and the use of keywords along with using a database from Google Scholar. The method used is bibliometric analysis. A total of 442 articles were collected from the Publish or Perish (PoP) application using the Google Scholar database which was then combined into 1 file with RIS format and entered into the VOSviewer application to obtain network visualization and visualization overlays. The results show that the trend of publications related to interactive learning media in mathematics education in Indonesia in the last five years (2016 - 2022) has increased every year, the most citations are in the organization "State University of Yogyakarta", in the journal JIPMat, in the article (Istiqlal, 2017). Adobe flash became the most cited learning media keyword. The keywords that became the new theme were Articulate storyline, ispring, discovery learning, interactive games, plane figure, and quadratic functions.